Plastic scintillator and its manufacturing method

The use of surface-treated bismuth oxide nanoparticles in plastic scintillators enhances dispersibility and transparency, addressing detection efficiency and temporal resolution issues, ensuring effective X-ray detection.

JP7611547B2Active Publication Date: 2025-01-10TOKYO PRINTING INC MFG CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021068191
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-14
Publication Date
2025-01-10
Estimated Expiration
2041-04-14

AI Technical Summary

Technical Problem

Existing plastic scintillators face challenges with low detection efficiency and luminescence amount due to limited dispersibility and high concentration of bismuth oxide, leading to reduced thickness and poor temporal resolution.

Method used

A plastic scintillator manufacturing method involving bismuth oxide nanoparticles surface-treated with hydroxyl-free and hydroxyl-containing carboxylic acids, combined with a polymerizable monomer and organic fluorescent compound, allowing high concentration dispersion and polymerization, resulting in high transparency and efficient light emission.

Benefits of technology

The method achieves high detection efficiency and temporal resolution with maintained luminescence, enabling effective X-ray detection through improved dispersibility and transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611547000001
    Figure 0007611547000001
Patent Text Reader

Abstract

To provide a plastic scintillator that is high in time resolution, counting rate and detection efficiency.SOLUTION: A plastic scintillator contains plastic, an organic fluorescent compound, and a metal oxide particle, where the metal oxide particle is a bismuth oxide nanoparticle surface-treated with a hydroxy group-free carboxylic acid and a hydroxy group-containing carboxylic acid. In the plastic scintillator set forth in Claim 1, the plastic may be a polymer of at least one aromatic vinyl and at least one methacrylate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a plastic scintillator used for radiation detection, and in particular to a plastic scintillator containing a metal oxide and a method for producing the same. [Background technology]

[0002] Generally, radiation, which is a charged particle such as alpha rays or beta rays, ionizes, excites or dissociates atoms or molecules in a material when passing through the material, losing energy. The energy transferred to the material is then emitted as thermal kinetic energy or electromagnetic waves. If the material is a fluorescent material, a large portion of the energy is emitted as light in the visible range; this phenomenon is called scintillation, and the emitted light is called scintillation light.

[0003] Similar scintillation occurs when uncharged radiation such as X-rays, gamma rays, and neutron rays interact with matter, releasing secondary charged particles, allowing radiation to be detected.

[0004] Materials that cause scintillation as described above are generally called scintillators, and are used in radiation detectors in a wide range of fields, including academic fields such as particle physics and material life science, as well as medicine and industry. Scintillators used in radiation detectors used in positron emission tomography (PET) and positron annihilation lifetime measurement devices are required to have high time resolution and detection efficiency in order to accurately determine the location where annihilation gamma rays are generated and obtain highly accurate images.

[0005] Scintillators are classified into inorganic scintillators and organic scintillators. Inorganic scintillators have the advantage of generally having high detection efficiency and large light emission due to their large effective atomic number, but many inorganic scintillators have problems with low achievable time resolution and counting rate due to the long decay time of their light emission. In addition, they have problems such as a low ratio of light-emitting components with short decay times, deliquescence, and increased background due to the radioactive nuclides contained in the scintillators themselves.

[0006] Examples of such inorganic scintillators include NaI(Tl) scintillators, BaF2 scintillators, and LaBr3(Ce). Although NaI(Tl) scintillators emit a relatively large amount of light, their decay time of emission is long at about 230 ns, resulting in poor time resolution. Although BaF2 scintillators contain short-lived components with a decay time of 0.6 ns, they also contain a large amount of long-lived components with a decay time of 620 ns, which accounts for about 75% of the total amount of emitted light, making them difficult to use for high count rate measurements. LaBr3(Ce) scintillators have a relatively short decay time of about 20 ns, but the crystal contains the radioactive nuclide 138La and 227Ac series nuclides mixed in as impurities, and have the disadvantage of having a background caused by their self-radioactivity.

[0007] On the other hand, a representative example of an organic scintillator is a so-called plastic scintillator, which is obtained by dissolving an organic light-emitting compound in a high molecular weight polymer such as polystyrene or polyvinyl toluene. For example, Non-Patent Document 1 describes several plastic scintillators. These plastic scintillators have the advantage of being able to achieve good time resolution and a high count rate because the decay time of luminescence is short compared to the inorganic scintillators, but they have the problem of low detection efficiency because the atomic numbers of the atoms (C, H, O, N) that make up the scintillator are small and the probability of electromagnetic interactions between X-rays or gamma rays and electrons in the scintillator is low.

[0008] Therefore, in order to increase the detection efficiency for X-rays and gamma rays, a plastic scintillator (EJ-256, ELJEN TECHNOELOGY) is commercially available in which polyvinyl toluene is filled with 1.5 to 5 mass% of lead, a heavy metal. However, since the amount of fill is small, a large increase in detection efficiency cannot be expected, and since lead is a harmful metal, it is desirable to avoid using it.

[0009] Several studies have been conducted to improve these problems. For example, the plastic scintillator in Patent Document 1 contains zirconium oxide nanoparticles or hafnium oxide nanoparticles that have been surface-treated with a hydroxyl-free carboxylic acid and a hydroxyl-containing carboxylic acid, and these can be dispersed at high concentrations in the plastic that is the base material of the plastic scintillator, so that it is said that high time resolution, high counting rate, and high detection efficiency can be achieved.

[0010] By the way, the electromagnetic interaction that occurs when detecting X-rays or gamma rays is a reaction with electrons, so it depends on the atomic number Z, which is equal to the number of electrons that an atom has. In particular, in the case of the photoelectric effect, which is the main reaction in the X-ray region, the reaction cross section τ is given by τ ∝ Z 5 Therefore, adding a heavy element with a large atomic number to a plastic scintillator is one effective way to increase the detection efficiency of the plastic scintillator.

[0011] Therefore, plastic scintillators have been proposed that use oxides of bismuth, an atom with a larger atomic number, such as plastic scintillators containing bismuth oxide particles surface-treated with phenylpropionic acid (Non-Patent Document 2) and bismuth oxide particles produced by a solvent evaporation method (Non-Patent Document 3). [Prior art documents] [Non-patent literature]

[0012] [Non-Patent Document 1] Radiation Measurement Using Scintillators Masaaki Kobayashi October 2014 [Non-Patent Document 2] Japanese Journal of Applied Physics, Vol. 57, 052203, 2018 [Non-Patent Document 3] Radiation Measurements, Vol. 135, 106361, 2020 [Patent documents]

[0013] [Patent Document 1] Patent No. 6810941 Summary of the Invention [Problem to be solved by the invention]

[0014] The plastic scintillators in Non-Patent Documents 2 and 3 claim that the detection efficiency could be increased by increasing the bismuth oxide content, but the content concentration is at most 10 to 20 mass %, and there are problems with dispersibility and transparency, so the thickness of the scintillator had to be thinned to 1 mm or less. In addition, as the bismuth oxide content is increased, the amount of light emitted is significantly reduced compared to EJ-256, so it cannot be said that a practical detection efficiency and amount of light emitted have been achieved.

[0015] SUMMARY OF THE PRESENT EMBODIMENTS An object of the present invention is to provide a plastic scintillator that has a high time resolution, a high counting rate and a high detection efficiency. [Means for solving the problem]

[0016] As a result of extensive research, the inventors have found that bismuth oxide nanoparticles surface-treated with a hydroxyl-free carboxylic acid and a hydroxyl-containing carboxylic acid can be dispersed at high concentrations in the plastic base material of a plastic scintillator, and as a result, a high counting rate and high detection efficiency can be achieved with high time resolution, thus completing the present invention.

[0017] That is, the present invention provides (1) Polymerizable Monomer an organic fluorescent compound; At least one acid selected from propionic acid, butyric acid and valeric acid is dissolved in water at 80 to 140°C under a nitrogen atmosphere. No hydroxyl groups Fatty Mono Carboxylic acids and hydroxyl-containing carboxylic acids By Surface-treated bismuth oxide nanoparticles A first step of mixing the above to obtain a dispersion; and a second step of polymerizing the polymerizable monomer in the resulting dispersion. Includes , plastic scintillator Manufacturing method , (2) The above Polymerizable Monomer The plastic scintillator according to (1), wherein the plastic scintillator is a polymer of at least one aromatic vinyl and at least one (meth)acrylate. Manufacturing method , (3) The plastic scintillator according to (1) or (2), wherein the hydroxyl-containing carboxylic acid is a hydroxyl-containing aliphatic monocarboxylic acid having 6 to 22 carbon atoms. Manufacturing method , (4) A plastic scintillator according to any one of (1) to (3), in which the content of the bismuth oxide nanoparticles as a metal oxide is 5% by mass or more and 70% by mass or less with respect to the total amount of the plastic scintillator. Manufacturing method , (5) The plastic scintillator according to any one of (1) to (4), wherein the organic fluorescent compound is at least one selected from 2-(4-biphenylyl)-5-phenyl-1,3,4-oxadiazole (PBD), 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole (Bu-PBD), p-terphenyl (P-TP), 2,5-diphenyloxazole (DPO), 1,4-bis[2-(5-phenyloxazolyl)]benzene (POPOP), 1,4-bis[2-(4-methyl-5-phenyloxazolyl)]benzene (DMPOPOP), 1,4-bis(2-methylstyryl)benzene (bis-MSB), benzophenone, and 4,4'''-bis(2-butyloctyloxy)-p-quaterphenyl (BIBUQ). Manufacturing method , It is. Effect of the Invention

[0018] The plastic scintillator of the present invention uses bismuth oxide nanoparticles that are surface-treated with hydroxyl-free carboxylic acid and hydroxyl-containing carboxylic acid, which are excellent in dispersibility, as metal oxide particles, and the plastic substrate is transparent and has excellent dispersibility with these metal oxide particles and organic fluorescent compounds, so that these metal oxide particles can be contained at high concentrations and have excellent transparency even at high concentrations. Therefore, it is possible to increase the detection efficiency for X-rays while maintaining the amount of light emission. If a pulse signal with sufficiently large and fast light emission is used, a high count rate and high time resolution can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described in detail. Note that this embodiment is merely one embodiment of the present invention, and the present invention is not limited to this embodiment, and various modifications and embodiments are possible without departing from the gist of the present invention.

[0020] In this specification, the symbol "to" indicates that the upper and lower limits are included, unless otherwise specified.

[0021] The plastic scintillator of the present invention is a plastic scintillator containing plastic, an organic fluorescent compound, and metal oxide particles, and the metal oxide particles are bismuth oxide nanoparticles that have been surface-treated with a hydroxyl-free carboxylic acid and a hydroxyl-containing carboxylic acid.

[0022] The plastic is a polymer of at least one aromatic vinyl and at least one (meth)acrylate.

[0023] Examples of the aromatic vinyl include aromatic compounds having a vinyl group, such as styrene, α-methylstyrene, and vinyltoluene.

[0024] The (meth)acrylate may be a monofunctional (meth)acrylate or a polyfunctional (meth)acrylate, and is not particularly selected, but at least one of a (meth)acrylate having an aromatic ring such as a benzene ring and a (meth)acrylate having a carboxylic acid is preferably used.

[0025] The (meth)acrylates having an aromatic ring such as a benzene ring are thought to contribute to improving compatibility with the portion of the plastic derived from the aromatic vinyl, and examples of such (meth)acrylates include 3-phenoxybenzyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, and benzyl (meth)acrylate.

[0026] Furthermore, the above-mentioned (meth)acrylates having a carboxylic acid are considered to contribute to improving the dispersibility of metal oxide particles, and examples thereof include 2-(meth)acryloyloxyethyl succinate and 2-(meth)acryloyloxyethyl phthalate.

[0027] The blending ratio of the aromatic vinyl to the (meth)acrylate in the polymer depends on the blending amount of the surface-treated bismuth oxide nanoparticles, but is preferably 2 to 20 parts by mass of the (meth)acrylate when the aromatic vinyl is taken as 100 parts by mass. If the (meth)acrylate is less than 2 parts by mass, the dispersibility of the surface-treated bismuth oxide nanoparticles decreases, and if it exceeds 20 parts by mass, the amount of light emitted decreases, failing to reach a level usable as a scintillator.

[0028] In this specification, "(meth)acrylate" is used to refer to both acrylate and methacrylate.

[0029] Examples of the organic fluorescent compound include p-terphenyl (P-TP), 2,5-diphenyloxazole (DPO), 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole (Bu-PBD), 1,4-bis[2-(5-phenyloxazolyl)]benzene (POPOP), 1,4-bis[2-(4-methyl-5-phenyloxazolyl)]benzene (DMPOPOP), 1,4-bis(2-methylstyryl)benzene (bis-MSB), benzophenone, 4,4'''-bis(2-butyloctyloxy)-p-quaterphenyl (BIBUQ), and the like, and at least one of these can be used. The content of the organic fluorescent compound is preferably 0.05% by mass or more and 10% by mass or less with respect to the obtained plastic scintillator. If the content of the organic fluorescent compound is less than 0.05% by mass, a sufficient amount of light emission cannot be obtained, whereas if the content of the organic fluorescent compound is more than 10% by mass, the amount of light emission decreases due to concentration quenching or the like.

[0030] The metal oxide particles used in the present invention are bismuth oxide nanoparticles that have been surface-treated with a hydroxyl-free carboxylic acid and a hydroxyl-containing carboxylic acid.

[0031] The hydroxyl group-free carboxylic acid includes aliphatic and aromatic monocarboxylic acids, and if it is aliphatic, it is a monocarboxylic acid having 3 to 22 carbon atoms, whether saturated or unsaturated, which may have a branched or aromatic substituent such as a phenyl group, and preferably has 3 to 8 carbon atoms. If it is less than 3, sufficient hydrophobicity cannot be imparted to the metal oxide particle surface, decreasing dispersibility with plastics and monomers, and if it exceeds 22, the surface tends to be sticky, and the molecular weight is large, so the amount of surface treatment increases, resulting in a decrease in the effective component of the bismuth oxide nanoparticles. Examples of aliphatic monocarboxylic acids include saturated monocarboxylic acids such as propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, octanoic acid, pelargonic acid, capric acid, neodecanoic acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, nonadecanoic acid, eicosanoic acid, heneicosanoic acid, and docosanoic acid, unsaturated fatty acids such as oleic acid, linoleic acid, linoleic acid, and fatty acids obtained by saponification and decomposition of fish oil, and geometric isomers thereof, as well as 3-phenylpropionic acid, cinnamic acid, etc. Hydroxyl-free aromatic monocarboxylic acids are monocarboxylic acids in which a carboxylic acid residue is directly bonded to an aromatic ring, and examples thereof include benzoic acid, toluic acid, etc.

[0032] The hydroxyl group-containing carboxylic acid is preferably a hydroxyl group-containing aliphatic monocarboxylic acid having 6 to 22 carbon atoms, whether saturated or unsaturated, which may be branched or may have an aromatic substituent such as a phenyl group. Specific examples include mevalonic acid, pantoic acid, 2-hydroxydecanoic acid, 3-hydroxyhexanoic acid, 2-hydroxystearic acid, 12-hydroxystearic acid, and ricinoleic acid.

[0033] The hydroxyl-free carboxylic acid is believed to contribute to the dispersion stability in the monomer or its polymer by imparting hydrophobicity to the surface of the bismuth oxide nanoparticles. Although the details of the hydroxyl-containing aliphatic carboxylic acid are unclear, it is believed that the hydroxyl group contributes to the dispersion stabilization by hydrogen bonding with the carbonyl group or carboxyl group between the bismuth oxide nanoparticles and the monomer or its polymer.

[0034] The bismuth oxide nanoparticles used in the present invention may be of any crystal form. However, since yellow coloring of the bismuth oxide nanoparticle powder significantly reduces the amount of light emitted by the plastic scintillator, it is preferable that the bismuth oxide nanoparticles are obtained as a white powder.

[0035] The bismuth oxide nanoparticles of the present invention may be produced by any method as long as they are surface-treated with a hydroxyl-free carboxylic acid and a hydroxyl-containing carboxylic acid, respectively. For example, the nanoparticles may be produced by mixing triphenylbismuthine with a hydroxyl-free carboxylic acid and a hydroxyl-containing carboxylic acid, and then reacting the resulting mixture at 80 to 140°C.

[0036] When the plastic is thermoplastic, the plastic scintillator of the present invention can also be produced by kneading the plastic with the organic fluorescent compound and bismuth oxide nanoparticles that have been surface-treated with the above-mentioned hydroxyl-free carboxylic acid and hydroxyl-containing carboxylic acid. However, in order to produce a plastic scintillator that has high transparency even when it contains a high concentration of bismuth oxide nanoparticles, it is preferable to mix and disperse a polymerizable monomer, the organic fluorescent compound, and the bismuth oxide nanoparticles that have been surface-treated with the above-mentioned hydroxyl-free carboxylic acid and hydroxyl-containing carboxylic acid, and then polymerize the polymerizable monomer in the resulting dispersion.

[0037] The polymerizable monomer includes at least one aromatic vinyl and at least one (meth)acrylate.

[0038] Examples of the aromatic vinyl include aromatic compounds having a vinyl group, such as styrene, α-methylstyrene, and vinyltoluene.

[0039] The (meth)acrylate may be a monofunctional (meth)acrylate or a polyfunctional (meth)acrylate, and is not particularly selected, but at least one of a (meth)acrylate having an aromatic ring such as a benzene ring and a (meth)acrylate having a carboxylic acid is preferably used.

[0040] Examples of the above-mentioned (meth)acrylate having an aromatic ring such as a benzene ring include 3-phenoxybenzyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, and benzyl (meth)acrylate.

[0041] Examples of the (meth)acrylate having a carboxylic acid include 2-(meth)acryloyloxyethyl succinate and 2-(meth)acryloyloxyethyl phthalate.

[0042] The plastic scintillator of the present invention can be produced by mixing and dispersing the polymerizable monomer, the organic fluorescent compound, and bismuth oxide nanoparticles that have been surface-treated with the above-mentioned hydroxyl-free carboxylic acid and hydroxyl-containing carboxylic acid, and then polymerizing the mixture by heating in the presence of a radical generator or by irradiating the mixture with active energy rays in the presence of a polymerization initiator.

[0043] The plastic scintillator obtained in this way is highly transparent even when it contains a high concentration of bismuth oxide nanoparticles, and can achieve high X-ray detection efficiency while maintaining light emission.

[0044] In the present invention, high transparency refers to a level at which a printed matter can be recognized by placing a test piece of a plastic scintillator on the printed matter, and specifically, an average transmittance of 60% or more for visible light (380 to 780 nm). EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples and comparative examples. In the examples and comparative examples, "parts" means "parts by mass" and "%" means "% by mass."

[0046] (Synthesis Example 1: Synthesis of bismuth oxide nanoparticles) 46.3g of triphenylbismuthine was added to a mixed solution of 26.9g of propionic acid and 26.9g of ricinoleic acid, and the mixture was stirred at 100°C for 5 hours under a nitrogen atmosphere to obtain a transparent solution. After cooling to room temperature, the transparent solution was added to 3L of acetone, filtered through a 0.2μm pore size filter, and the resulting white matter was vacuum dried at 60°C for one day and night to obtain 33.6g of bismuth oxide powder surface-treated with carboxylic acid. The amount of surface treatment with carboxylic acid was 35.48% based on the mass reduction rate when heated to 800°C at a rate of 40°C / min under a nitrogen atmosphere using a PerkinElmer thermogravimetric analyzer TGA8000, and the crystallite diameter was 5.4nm based on XRD.

[0047] In the present invention, the average particle diameter of bismuth oxide nanoparticles was measured using an X-ray diffractometer (Rigaku Corporation, fully automatic multipurpose X-ray diffractometer SmartLab) under measurement conditions of an X-ray tube voltage of 40 kV, an X-ray tube current of 30 mA, and a scanning range of 2θ of 10.0-65.0°. The half-width β was calculated from the diffraction intensity from the (200) plane near 2θ=32.67° in the X-ray diffraction measurement, and the crystallite diameter D was calculated using the Scherrer formula of the following equation 1, with the Scherrer constant K being 0.9 and the wavelength λ of the X-ray tube being 1.54059, and this value was used as the average particle diameter.

[0048] (Number 1) D=K λ / (β cosθ)

[0049] The bismuth oxide nanoparticles of Synthesis Example 1 were used to produce the plastic scintillators of Examples 1 to 8 below.

[0050] Example 1 1.1 parts of the bismuth oxide nanoparticles of Synthesis Example 1, 9.1 parts of styrene monomer, 0.2 parts of 3-phenoxybenzyl acrylate, 0.2 parts of 2-acryloyloxyethyl succinate, and 0.3 parts of 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole were added to a vial and ultrasonically dispersed. After the mixture became transparent, 0.08 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and the mixture was left to stand in a 65°C oven under a nitrogen atmosphere for 24 hours to obtain a plastic scintillator containing 10% bismuth oxide.

[0051] Example 2 A plastic scintillator containing 20% ​​bismuth oxide was obtained in the same manner as in Example 1, except that the amount of bismuth oxide nanoparticles was changed to 2.5 parts.

[0052] Example 3 4.3 parts of the bismuth oxide nanoparticles of Synthesis Example 1, 8.6 parts of styrene monomer, 0.5 parts of 3-phenoxybenzyl acrylate, 0.5 parts of 2-acryloyloxyethyl succinate, and 0.3 parts of 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole were added to a vial and ultrasonically dispersed. After the mixture became transparent, 0.08 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and the mixture was left to stand in a 65°C oven under a nitrogen atmosphere for 24 hours to obtain a plastic scintillator containing 30% bismuth oxide.

[0053] Example 4 6.7 parts of the bismuth oxide nanoparticles of Synthesis Example 1, 8.1 parts of styrene monomer, 1.4 parts of 2-acryloyloxyethyl succinate, and 0.3 parts of 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole were added to a vial and ultrasonically dispersed. After the mixture became transparent, 0.08 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and the mixture was left to stand in an oven at 65°C for 24 hours under a nitrogen atmosphere to obtain a plastic scintillator containing 40% bismuth oxide.

[0054] Example 5 1.1 parts of the bismuth oxide nanoparticles of Synthesis Example 1, 9.1 parts of vinyltoluene monomer, 0.2 parts of 3-phenoxybenzyl acrylate, 0.2 parts of 2-acryloyloxyethyl succinate, and 0.3 parts of 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole were added to a vial and ultrasonically dispersed. After the mixture became transparent, 0.08 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and the mixture was allowed to stand in a 65°C oven under a nitrogen atmosphere for 24 hours to obtain a plastic scintillator containing 10% bismuth oxide.

[0055] Example 6 A plastic scintillator containing 20% ​​bismuth oxide was obtained in the same manner as in Example 5, except that the amount of bismuth oxide nanoparticles was changed to 2.5 parts.

[0056] Example 7 4.3 parts of the bismuth oxide nanoparticles of Synthesis Example 1, 8.6 parts of vinyltoluene monomer, 0.5 parts of 3-phenoxybenzyl acrylate, 0.5 parts of 2-acryloyloxyethyl succinate, and 0.3 parts of 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole were added to a vial and ultrasonically dispersed. After the mixture became transparent, 0.08 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and the mixture was allowed to stand in a 65°C oven under a nitrogen atmosphere for 24 hours to obtain a plastic scintillator containing 30% bismuth oxide.

[0057] Example 8 6.7 parts of the bismuth oxide nanoparticles of Synthesis Example 1, 8.1 parts of vinyltoluene monomer, 1.4 parts of 2-acryloyloxyethyl succinate, and 0.3 parts of 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole were added to a vial and ultrasonically dispersed. After the mixture became transparent, 0.08 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and the mixture was allowed to stand in an oven at 65°C for 24 hours under a nitrogen atmosphere to obtain a plastic scintillator containing 40% bismuth oxide.

[0058] The plastic scintillator obtained in each Example was molded into a cylinder having a diameter of 8 mm and a height of 3 mm to prepare an evaluation sample.

[0059] Comparative Example 1 A plastic scintillator (EJ-256, ELJEN TECHNOELOGY) containing 5% lead and molded to a diameter of 8 mm and a height of 3 mm was used as Comparative Example 1 (standard for evaluating the amount of light emitted).

[0060] For the plastic scintillators obtained in each of the Examples and Comparative Examples, the average light transmittance, luminescence amount, and detection efficiency for visible light (380 to 780 nm) were determined by the following methods. The results are summarized in Table 1.

[0061] (Average light transmittance) For the evaluation samples of Examples 1 to 8, the light transmittance of 380 to 780 nm, which corresponds to visible light, was measured at 0.5 nm intervals using an ultraviolet-visible-near infrared spectrophotometer (UH4150, manufactured by Hitachi High-Tech Science Corporation), and the arithmetic average was calculated.

[0062] (Light output) The evaluation sample of each Example was irradiated with 67.4 keV X-rays, and the scintillation light was detected by a photomultiplier tube (product name: R7400P, manufacturer: Hamamatsu Photonics). The detection signal pulse height spectrum obtained by amplifying the detected signal by a charge-sensitive preamplifier (product name: 2005, manufacturer: Canberra) was used to determine the channel number of the peak position (peak channel number) for each Example. For the scintillator of Comparative Example 1, the peak channel number was determined in the same manner as above, and this was used as the reference peak channel number. The ratio of the peak channel number of each example to this reference peak channel number was determined, and this was taken as the amount of light emitted per energy of the incident X-ray (photons / MeV).

[0063] (detection efficiency) Under the same conditions as in the measurement of the amount of luminescence, a 5 mm thick NaI(Tl) scintillator (product name: SP-10, manufacturer: Oyo Koken Kogyo Co., Ltd.) was measured, and the area of ​​the detection signal pulse-height spectrum of each Example was calculated when the area of ​​the obtained detection signal pulse-height spectrum was set to 100. This value corresponds to the total number of detected events, and this value was taken as the detection efficiency (%).

[0064] [Table 1]

Claims

1. A polymerizable monomer, An organic fluorescent compound; Bismuth oxide nanoparticles that have been surface-treated with at least one hydroxyl-free aliphatic monocarboxylic acid and a hydroxyl-containing carboxylic acid selected from propionic acid, butyric acid, and valeric acid under conditions of 80 to 140° C. in a nitrogen atmosphere; A first step of mixing the above to obtain a dispersion; and a second step of polymerizing the polymerizable monomer in the resulting dispersion. A method for producing a plastic scintillator, comprising:

2. 2. The method for producing a plastic scintillator according to claim 1, wherein the polymerizable monomer is a polymer of at least one aromatic vinyl and at least one (meth)acrylate.

3. 3. The method for producing a plastic scintillator according to claim 1, wherein the hydroxyl-containing carboxylic acid is a hydroxyl-containing aliphatic monocarboxylic acid having 6 to 22 carbon atoms.

4. 4. A method for producing a plastic scintillator according to claim 1, wherein the content of the bismuth oxide nanoparticles as a metal oxide is 5% by mass or more and 70% by mass or less relative to the total amount of the plastic scintillator.

5. The method for producing a plastic scintillator according to any one of claims 1 to 4, wherein the organic fluorescent compound is at least one selected from 2-(4-biphenylyl)-5-phenyl-1,3,4-oxadiazole (PBD), 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole (Bu-PBD), p-terphenyl (P-TP), 2,5-diphenyloxazole (DPO), 1,4-bis[2-(5-phenyloxazolyl)]benzene (POPOP), 1,4-bis[2-(4-methyl-5-phenyloxazolyl)]benzene (DMPOPOP), 1,4-bis(2-methylstyryl)benzene (bis-MSB), benzophenone, and 4,4'''-bis(2-butyloctyloxy)-p-quaterphenyl (BIBUQ).

Citation Information

Patent Citations

  • Plastic scintillator and method for producing the same

    JP2021031648A

  • Plastic scintillator and its manufacturing method

    JP6810941B1

  • Plastic scintillators with high loading of one or more metal carboxylates

    US20160102247A1